The Advancement of Civilization and the Causes of the Destruction of the People of Thamud in the Qur’an - Tupan, Naufal Akmaldi Putra; Al Ghifari, Charisma Zain; Altafini, Muhammad Zafi; Rahma, Najwa Farida (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
<div class="[–thread-content-max-width:32rem] @[34rem]:[–thread-content-max-width:40rem] @[64rem]:[–thread-content-max-width:48rem] mx-auto flex max-w-(–thread-content-max-width) flex-1 text-base gap-4 md:gap-5 lg:gap-6 group/turn-messages focus-visible:outline-hidden" tabindex="-1"> <div class="min-h-8 text-message relative flex w-full flex-col items-end gap-2 text-start break-words whitespace-normal [.text-message+&]:mt-5" dir="auto" data-message-author-role="assistant" data-message-id="faa5a999-6761-4eb0-ad2c-d63672a5276e" data-message-model-slug="gpt-4o"> This study examines the story of the people of Thamud as portrayed in the Qur’an to understand the dynamics of a civilization’s advancement and eventual downfall. The Thamud people demonstrated rapid progress in technology and architecture, such as their ability to carve dwellings out of stone and achievements in agriculture. However, this progress ultimately led to arrogance, rejection of monotheistic teachings, and unjust treatment of the Prophet Salih. The study aims to answer: How does the Qur’an depict the Thamud civilization, and what theological, sociological, and moral factors contributed to its destruction? Using a qualitative descriptive method with a thematic exegesis approach and historical analysis, this research investigates Qur’anic verses in Surahs Al-A’raf and Hud, supported by both classical and contemporary tafsir sources. The findings show that a technically advanced civilization can collapse if it lacks a strong spiritual and moral foundation. The downfall of Thamud was caused by collective rebellion, moral decadence, social elitism, and the rejection of divine signs. This story serves as an important reflection for modern society to maintain a balance between progress and divine values.